A Magnetoclick Imidazolidinone Nanocatalyst for Asymmetric 1, 3‐Dipolar Cycloadditions. Issue 18 (27th November 2013) - Pagoti, Sreenivasarao; Dutta, Debasish; Dash, Jyotirmayee
Abstract A 1, 3‐dipolar azide–alkyne cycloaddition has been used to prepare a magnetic nanoparticle immobilized MacMillan catalyst that catalyzes the enantioselective 1, 3‐dipolar cycloaddition between nitrones and α, β‐unsaturated aldehydes. The catalyst can be recovered and recycled for five consecutive runs without any significant loss in yields and diastereo‐ and enantioselectivities of the isoxazolidines. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>